Determination of Position-Orientation Matrix for a Planar Parallel Topology Robot by Using the “Pair of Frames” Concept - Calin-Octavian Miclosina; Ioan Halalae (Robotica & Management, 2019)
The paper presents a method of determining the position-orientation matrix of the reference system attached to the characteristic point of a planar parallel topology robot, by using the “connexion” and “pair of frames” concepts. The kinematical scheme of robot’s guiding device mechanism of FP3+3•RTR+MP3 type is shown, as well as the manner of choice of the frames attached to the links. In order to obtain the position-orientation matrix, the matrix calculus is accomplished.